DIFFERENCES IN MATHEMATICS ANXIETY AND MATHEMATICS CONNECTION ABILITY IN GENDER PERSPECTIVE - Mira Nofita Sari; Elda Herlina; Ummul Huda (AGENDA: Jurnal Analisis Gender dan Agama, 2021)
This research is a comparative study with quantitative methods. This study aims to: 1) find out whether there are differences in mathematical connection abilities between male and female students, 2) find out whether there are differences in math anxiety between male and female students, 3) find out whether there is an interaction between math anxiety and gender with mathematical connection ability. Data were obtained from anxiety questionnaire sheets and mathematical connection ability tests. Then it was analyzed by two-way analysis of variance and the Mann-Whitney test. The results show that: 1) There is no difference in mathematical connection ability between male and female students, 2) There is a difference in math anxiety between male and female students, 3) There is no interaction between math anxiety and gender on mathematical connection ability.